Răspuns :
1. a) 12 · 7 + 12 · 3 = 12 · (7 + 3) = 12 · 10 = 120.
b) 6 · 10 + 12 · 10 + 17 · 10 = 10 · (6 + 12 + 17) = 10 · 35 = 350.
c) 14 · 22 - 14 · 10 - 14 = 14 · (22 - 10 - 1) = 14 · 11 = 154.
d) 5 · 35 + 5 · 70 - 5 · 5 = 5 · (35 + 70 - 5) = 5 · 100 = 500.
e) 43 · 275 + 57 · 275 = 275 · (43 + 57) = 275 · 100 = 27500.
2. a) 2a + 2b + 2c = 2 · (a + b + c).
b) 5x + 5y - 5z = 5 · (x + y - z).
c) 7a + 7b + 49 = 7 · (a + b + 7).
d) 3x - 3y + 3 = 3 · (x - y + 1).
3. x = 3; y + z = 10.
a) 7x + 7y + 7z = 7 · (x + y + z) = 7 · (3 + 10) = 7 · 13 = 91.
b) 17x + 17y + 17z - 10 = 17 · (x + y + z) - 10 = 17 · 13 - 10 = 221 - 10 = 211.
c) 5x + 10y + 10z = 5 · 3 + 10 · (y + z) = 15 + 10 · 10 = 15 + 100 = 115.
d) nu se vede în poză tot exercițiul.
4. (11 + 22 + 33 + ... + 99) : (1 + 2 + 3 + ... + 9) =
= 11 · (1 + 2 + 3 + ... + 9) : (1 + 2 + 3 + ... + 9) =
= 11 · 1 = 11.
5. a) ab + ac = 520
b + c = 52
~
a · (b + c) = 520
a · 52 = 520 /:52
a = 10.
~
b) ab - ac = 45
b - c = 9
~
a · (b - c) = 45
a · 9 = 45 /:9
a = 5.
~
c) ab + ac + 70 = 170
a = 25
~
25 · (b + c) + 70 = 170 /-70
25 · (b + c) = 100 /:25
b + c = 4.
~
d) ab - ac - 48 = 2
a = 10
~
10 · (b - c) - 48 = 2 /+48
10 · (b - c ) = 50 /:10
b - c = 5.
~
/robertinni
b) 6 · 10 + 12 · 10 + 17 · 10 = 10 · (6 + 12 + 17) = 10 · 35 = 350.
c) 14 · 22 - 14 · 10 - 14 = 14 · (22 - 10 - 1) = 14 · 11 = 154.
d) 5 · 35 + 5 · 70 - 5 · 5 = 5 · (35 + 70 - 5) = 5 · 100 = 500.
e) 43 · 275 + 57 · 275 = 275 · (43 + 57) = 275 · 100 = 27500.
2. a) 2a + 2b + 2c = 2 · (a + b + c).
b) 5x + 5y - 5z = 5 · (x + y - z).
c) 7a + 7b + 49 = 7 · (a + b + 7).
d) 3x - 3y + 3 = 3 · (x - y + 1).
3. x = 3; y + z = 10.
a) 7x + 7y + 7z = 7 · (x + y + z) = 7 · (3 + 10) = 7 · 13 = 91.
b) 17x + 17y + 17z - 10 = 17 · (x + y + z) - 10 = 17 · 13 - 10 = 221 - 10 = 211.
c) 5x + 10y + 10z = 5 · 3 + 10 · (y + z) = 15 + 10 · 10 = 15 + 100 = 115.
d) nu se vede în poză tot exercițiul.
4. (11 + 22 + 33 + ... + 99) : (1 + 2 + 3 + ... + 9) =
= 11 · (1 + 2 + 3 + ... + 9) : (1 + 2 + 3 + ... + 9) =
= 11 · 1 = 11.
5. a) ab + ac = 520
b + c = 52
~
a · (b + c) = 520
a · 52 = 520 /:52
a = 10.
~
b) ab - ac = 45
b - c = 9
~
a · (b - c) = 45
a · 9 = 45 /:9
a = 5.
~
c) ab + ac + 70 = 170
a = 25
~
25 · (b + c) + 70 = 170 /-70
25 · (b + c) = 100 /:25
b + c = 4.
~
d) ab - ac - 48 = 2
a = 10
~
10 · (b - c) - 48 = 2 /+48
10 · (b - c ) = 50 /:10
b - c = 5.
~
/robertinni